Nanobiotechnology in diagnosis, drug delivery and treatment - Rai, Mahendra; Razzaghi Abyaneh, M.; Ingle, Avinash P. (Wiley-Blackwell, 2020)
"Nanotechnology is considered as the most rapidly growing technology in the world. Considering the enormous applications of nanotechnology in various fields including biomedicine, it is believed as the beginning of a new era and industrial revolution of the twenty-first century. Nanotechnology has proved its potential of providing completely novel and unique concepts and approaches in medicine which facilitates the development of efficient, rapid and sensitive diagnosis as well as treatment strategies with the least possible interventions and almost without adverse effects"-- Provided by publisher.
Keywords: Nanomedicine -- Methods.; Nanoparticles -- Therapeutic use.; elektronické knihy; electronic books